A State of Mixture : Christians, Zoroastrians, and Iranian Political Culture in Late Antiquity - Payne, Richard E., 1981- (Book collections on Project MUSE., 2015)
"A State of Mixture seeks to resolve the paradox of how East Syrian Christian communities flourished in a Zoroastrian political system, the Iranian Empire. If previous studies have regarded Christians as marginal, insular, and often persecuted, the present book demonstrates their integration into elite networks, adoption of Iranian political practices and imaginaries, and participation in imperial institutions. The rise of Christianity in Iran depended on the Zoroastrian theory and practice of hierarchical, differentiated inclusion, according to which Christians, Jews, and others occupied legitimate places in Iranian political culture in positions subordinate to the imperial religion. Christians, for their part, positioned themselves in a political culture not of their own making with recourse to their own ideological and institutional resources, ranging from the writing of saints' lives to the judicial arbitration of bishops. In placing the social history of East Syrian Christians at the center of the Iranian imperial story, A State of Mixture helps to explain the endurance of a culturally diverse empire across four centuries"--Provided by publisher.